Time travelling girls: bravery, know-how and can-do in girl volunteers at Fort Edmonton Park - Fitzsimmons Frey, Heather (My University, 2022)
Editor's note: Costumed interpretation is also the subject of Dr. Frey and Gigliotti, who work with Fort Edmonton Park in Canada. Utilizing observations and interviews with girls volunteering as interpreters, Frey and Gigliotti reflect on how flexible first and third-person interpretation provides an interpretive tool to understand both the historic and modern lives of girls. Notably, Fort Edmonton’s girl volunteers become activists in re-performing the past, countering traditional narratives of gender, age, and history at the Fort while also challenging visitor assumptions about the abilities of modern girls.
Keywords: Fort Edmonton Park; interpretation; interviews